2002
DOI: 10.1016/s0022-5347(05)65468-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Bladder Carcinoma Cell Adhesion by Oligopeptide Combinations in Vitro and in Vivo

Abstract: Combining oligopeptides with various specificities significantly inhibited tumor cell adhesion and tumor outgrowth. Application of this principle in a clinical setting may be an effective method for reducing the recurrence rate of superficial bladder cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 50 publications
2
17
0
Order By: Relevance
“…Both the α3β1 and α5β1 integrin family members may be of particular relevance in the context of re-seeding of tumor cells post-TURBT in NMIBC. In addition to the efficacy results shown here, the notion that integrins mediate UCC seeding is further supported by earlier work where α5β1-specific and α3β1-specific ECM-blocking oligopeptides used in combination were able to effectively inhibit orthotopic MB49 tumor implantation (11) and in another more recent report where shRNA knockdown of α3 resulted in impaired establishment of human T24 UCCs in a subcutaneous xenograft model (13).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Both the α3β1 and α5β1 integrin family members may be of particular relevance in the context of re-seeding of tumor cells post-TURBT in NMIBC. In addition to the efficacy results shown here, the notion that integrins mediate UCC seeding is further supported by earlier work where α5β1-specific and α3β1-specific ECM-blocking oligopeptides used in combination were able to effectively inhibit orthotopic MB49 tumor implantation (11) and in another more recent report where shRNA knockdown of α3 resulted in impaired establishment of human T24 UCCs in a subcutaneous xenograft model (13).…”
Section: Discussionsupporting
confidence: 83%
“…Re-seeding may be facilitated, in part, by the interaction of tumor cell integrins with extracellular matrix (ECM) components including fibronectin, laminin, and collagen, all of which are likely to be exposed at the surgical site following resection. Previous reports have indicated that specific mammalian integrins, particularly integrin heterodimer family members alpha3beta1 (α3β1) and alpha5beta1 (α5β1), are implicated as being required for the attachment of tumor cells to the ECM and establishment of tumors in the urothelium in vivo (11)(12)(13).…”
Section: Been Previously Characterized As An Integrin-specific Oncolymentioning
confidence: 99%
See 1 more Smart Citation
“…EILDV had shown efficacy in inhibiting bladder cell adhesion on a fibronectin monomatrix, while in the natural environment of the murine bladder EILDV alone was ineffective in inhibiting tumour outgrowth [7]. Yamamoto et al .…”
Section: Discussionmentioning
confidence: 99%
“…In the ECM of the bladder wall fibronectin, collagen, and laminin are the main promoters of cell attachment [6]. Previous studies have shown more effective inhibition of tumour cell adhesion by combining integrin receptor‐blocking oligopeptides with different binding specifities as compared with using single oligopeptides [7]. In the present study, our primary goal was to evaluate a novel mixture of oligopeptides for its anti‐adhesive properties.…”
Section: Introductionmentioning
confidence: 99%